Sustainable Development of Business in Our Country and Foreign Experiences - Dosent, Dexkanova Nilufar Sagdullayevna; Murodov Nodir; Shernazarov Murod (Genius Journals, 2024)
The article examines entrepreneurial activity in our country, its current state, achieved results, priority areas of development and foreign experience.
Keywords: Entrepreneurship; economic reforms; economic growth